PENGARUH PENGGUNAAN MEDIA FLASH CARD TERHADAP HASIL BELAJAR MATEMATIKA SISWA SLOW LEARNER - M Ferry Irawan; Alia Latifah; Nikentari Rizky (Jurnal Dedikasi Pendidikan, 2024)
Students with slower learning abilities face difficulties in receiving information. Therefore, they require engaging learning media, and one of them is the use of learning cards. This research aims to evaluate the impact of using learning cards in teaching mathematics, specifically in the topic of spatial structures, on the learning outcomes of students with slower learning abilities at Madrasah Ibtidaiyah. This study employs a quasi-experimental method at Madrasah Ibtidaiyah Negeri OKU Timur in the academic year 2022/2023. The research design adopts a time series format, and data analysis is carried out using an associative hypothesis testing method. The analysis results show a Z value of 2.70, exceeding the critical value of 1.96. Therefore, H0 is rejected, and H1 is accepted. This finding indicates a significant influence of using learning cards on improving the mathematics learning outcomes of students with slower learning abilities. The pretest data reveals an average score of 54.4, while the posttest data yields an average score of 77.2. This analysis indicates a significant difference between mathematics learning outcomes before and after the implementation of learning cards. The average learning outcomes increased after using learning cards, demonstrating the effectiveness of this media in enhancing the understanding of students with slower learning abilities regarding spatial structures